2014
DOI: 10.1111/acer.12562
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Alcohol Exposure Alters GABAA Receptor Subunit Expression in Adult Hippocampus

Abstract: Background-The long-term consequences of adolescent alcohol abuse that persist into adulthood are poorly understood and have not been widely investigated. We have shown that intermittent exposure to alcohol during adolescence decreased the amplitude of GABA A receptormediated tonic currents in hippocampal dentate granule cells in adulthood. The aim of the present study was to investigate the enduring effects of chronic intermittent alcohol exposure during adolescence or adulthood on the expression of hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
1
24
0
3
Order By: Relevance
“…In particular, extrasynaptic GABA A receptors have been shown to be highly sensitive to EtOH (Wallner et al, 2003), and we recently showed that AIE reduced tonic inhibition in dentate granule cells from adult rats to levels typically seen in adolescents (Fleming et al, 2013). We have also determined that the GABA A delta receptor subunit, which drives tonic inhibition, is significantly reduced after AIE in whole hippocampal samples (Centanni et al, 2014). Further work will be necessary to determine whether these changes in tonic inhibition are driving excitatory changes within the CA1 network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, extrasynaptic GABA A receptors have been shown to be highly sensitive to EtOH (Wallner et al, 2003), and we recently showed that AIE reduced tonic inhibition in dentate granule cells from adult rats to levels typically seen in adolescents (Fleming et al, 2013). We have also determined that the GABA A delta receptor subunit, which drives tonic inhibition, is significantly reduced after AIE in whole hippocampal samples (Centanni et al, 2014). Further work will be necessary to determine whether these changes in tonic inhibition are driving excitatory changes within the CA1 network.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AIE has been shown to reduce A-type potassium current ( I A ) in GABAergic hippocampal interneurons (Li et al, 2013), GABA A receptor-mediated tonic current in dentate granule cells (Fleming et al, 2012, 2013) in adulthood, and protein levels of delta and alpha-4 GABA receptors in whole hippocampus (Centanni et al, 2014), while comparable EtOH exposure during adulthood did not produce equivalent long-lasting changes in these cellular functions or receptor proteins. Thus, not only does adolescent EtOH exposure promote long-lasting changes in hippocampal cellular function, but that adolescence is also a period of distinctive vulnerability to the long-term effects of EtOH, enduring even after an extended period of abstinence.…”
mentioning
confidence: 99%
“…Prior surface-expressed proteins used as controls (Na-K-ATPase) are well-known to be altered by ethanol exposure (Wang et al, 2009; Santos et al, 2017). Therefore, equal amounts of loaded protein samples were similarly quantified as elsewhere (Diaz et al, 2011; Centanni et al, 2014). Optical densities for cell surface receptors were normalized to matched water controls within the same blot.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, rats subjected to adolescent intermittent alcohol (AIE) exposure between PD 30 and PD46 showed a significant reduction in the δ subunit protein levels in the absence of any changes in mRNA, at both 48 h and 26 days after the last alcohol exposure (Centanni et al . ). The α4 subunit protein levels were significantly reduced, but mRNA levels were increased, 26 days (but not 48 h) after the last AIE exposure.…”
Section: Evidence For Gabaa Receptor Involvement In Addictionmentioning
confidence: 97%